Chemical stability of silicon nitride coatings used in the crystallization of photovoltaic silicon ingots. Part II: Stability under argon flow. Issue 1 (January 2017) - Drevet, B.; Selzer, A.; Brizé, V.; Voytovych, R.; Camel, D.; Eustathopoulos, N.
Abstract: Processing of photovoltaic silicon by solidification is currently carried out under argon flow in silica crucibles coated with an oxidized silicon nitride powder. A series of experiments was performed to study the reactions between coating components under argon flow by varying the temperature, the holding time and the oxygen content in the coating. The results are discussed with the help of a simple analytical model taking into account the diffusive transport of gaseous reaction species from the inside of the porous coating to the flowing argon. The conclusions drawn are used to discuss different practical aspects of the photovoltaic silicon crystallization process.